Integrasi Kurikulum Pesantren Dalam Kurikulum 2013 Di SMK Al-Munawwir Krapyak Yogyakarta - Ade Putri Wulandari (STAI Terpadu Yogyakarta, 2020)
Integrated curriculum in formal schools under the auspices of Islamic boarding schools is implemented in order to produce graduates who excel in the field of general knowledge and uphold Islamic values. So that it can produce students who are experts in the field of religion while excelling in general knowledge to be able to compete with other graduates in this 4.0 era. This research takes place in the Al-Munawwir Krapyak Vocational School in Yogyakarta which is a school under the auspices of Islamic boarding schools that implement an integrated curriculum. This study aims to answer the question of how to integrate the pesantren curriculum into the 2013 Curriculum at SMK Al-Munawwir Krapyak Yogyakarta. This type of research is a qualitative study using the analysis of the Miles and Huberman models. The results showed that the integration of pesantren curriculum in 2013 curriculum at Al-Munawwir Vocational School in Krapyak Yogyakarta was by increasing the content of pesantrenan by breaking up PAI subjects into fiqh subjects, al-quran hadith, moral creed, SKI then Arabic subjects. The integration model implemented at Al-Munawwir Krapyak Yogyakarta Vocational School is the first model, the integration model into the curriculum package.